PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI DI KOTA MAKASSAR - Sulfadli . (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2019)
This study aims to determine the effect of local revenue and balancing funds on economic growth in the City of Makassar. The data used are secondary data during 5 years (2008-2012). Data were analyzed using multiple linear regression. The results of this study indicate that Regional Original Income (PAD) has a positive and not significant effect on economic growth and the Balancing Fund (DP) has a positive and not significant effect on economic growth in Makassar City.